The flipped classroom: changing the response to the needs of students - Alba García Barrera (Avances en Supervisión Educativa, 2013)
Technological tools and internet use, seems to be gaining an increasing relevance in the classroom. However, the use made of them does not always respond to the real needs posed by students in their learning and skills acquisition. This article offers a new perspective to meet the educational needs of students through the use of information and communication technologies. Specifically, the recent methodology known as classroom flipped classroom or reverse could help facilitate this process by raising educational sessions very different to what we actually know. Perhaps we are witnessing the classroom of the future …